Los impactos económicos, sociales y medioambientales negativos en el ecoturismo: una revisión de la literatura - Orgaz Agüera, Francisco (Nómadas. Critical Journal of Social and Juridical Science, 2015)
Ecotourism is configured as a type of tourism that it is developing in contact with the nature. This tourism also helps to improve the socio-economic development of local communities and promotes the conservation of natural resources and respect for the environment. Although, ecotourism also generates significant negative impacts. The objective of this research is to analyze different economic, social and environmental impacts that ecotourism can cause on the destination. The methodology has consisted of a review of the scientific literature. The results show that ecotourism can generate various negative impacts on the destination.